Strategi Pembelajaran PAI Berbasis Nilai Keadilan Gender Dan Inklusivitas - Jamiatul Haerat; Dika Tripitasari; Ahdar Ahdar; Abd. Wahid (Universitas Islam DDI A.G.H Abdurrahman Ambo Dalle, 2026)
This study aims to analyze the learning strategy of Islamic Religious Education (PAI) based on value acculturation in the application of gender justice and inclusivity in the educational environment. This research is a narrative literature review method with a qualitative-descriptive approach through the search of various scientific journals, books, and previous research results that are relevant to the themes of Islamic education, gender justice, inclusivity, and value acculturation. The data was analyzed using thematic analysis to identify patterns, concepts, and forms of value integration in PAI learning. The results of the study show that the PAI learning strategy based on value acculturation is able to create a more contextual, fair, and inclusive learning process through discussion methods, problem solving, role play, and case studies that encourage active participation of students. The integration of gender justice and inclusivity values in PAI learning not only strengthens students' cognitive understanding of Islamic teachings, but also shapes social awareness, empathy, respect for differences, and fair attitudes in daily life. This strategy also strengthens the role of teachers as value facilitators in building a humanistic learning culture that is responsive to the diversity of students.